ASSESSING THE APPLICATION OF GEOGRAPHIC INFORMATION SYSTEM (GIS) AMONG AGRICULTURAL-BASED RESEARCHERS IN SOUTHWESTERN NIGERIA - Ojo, T. F.; Famakinwa, M.; Omonijo, O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
This study assessed the application of Geographic Information System (GIS) tools among agricultural-based researchers in southwestern Nigeria. It specifically described the personal and socio-economic characteristics of agricultural-based researchers, determined their level of awareness in the use of GIS, examined their perception about GIS and assessed the application of GIS by agricultural-based researchers. A two-stage sampling procedure was used to select 150 respondents from six public universities with faculties of Agriculture using proportionate sampling technique which translated into 36, 22, 24, 22, 25 and 23 respondents from OAU, OOU, FUTA, UniOsun, FUNNAB and LAUTECH respectively. Data were gathered through structured questionnaire and analyzed using descriptive statistics such as frequency count, percentages and mean while correlation and chi-square analyses were used to make inferential deductions. The results show that the respondents had a mean age of 42.9 ± 9.8 years and 56.0% had obtained Ph.D. degree. The mean year of experience as researchers was 14.5 ± 6.8 years. Majority (86.9%) of them has heard about GIS. There were significant associations between respondents’ application of GIS and their sources of fund for research (χ2= 33.483; ρ≤ 0.01) and researchers’ academic qualification (χ2= 29.502; ρ≤ 0.01). There was a negative and significant relationship between respondents’ application of GIS and their years of experience (r=-0.130; ρ≤ 0.01). The study concluded that many of the respondents have heard about GIS but have not been applying it in their research endeavour and need to be trained on how to explore the potentials of GIS in their research for better results.